PENERAPAN LATIHAN UNIT TERHADAP HASIL MENYERANG SEPAK BOLA CLUB JARAH FC DI KABUPATEN SINTANG - Wahyudi, Diky; Hidasari, Fitriana Puspa; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractIdentification of the problem refers to the background that has been described and formulated problems that will be examined such as, the training patterns that have been given have not been pioneered, experienced difficulties and failure of players when attacking, team failure when competing because it is difficult to score goals, weak techniques and the skill of each athlete both individually and in teams, physical conditions are weak, so that each training session is not complete. The purpose of this study was to determine the effect of the application of unit training on the results of attacking football at the Jarah Club in Sintang Regency. This research method is an experiment in the form of one group pretest-posttes. the population of Jarah Club players in the Sintang Regency totaling 25 players, sampling using the total sampling method, the researchers took all of the population, with a total sample of 25 students. This research technique uses tests and measurements, namely tests with a lattice measurement instrument soccer performance. Data analysis using t-test formula. With an increase in the average attack result at the Jarah Football club in Sintang Regency the pretest was 34.32, while the posttest was 50.88 (an increase of 16.56 points) so there was an increase of 48.25%. Thus the application of the exercise unit affects the results of attacking on soccer games in the Jintang Club, Sintang Regency. Keywords: unit training, results of attacking soccer.